Oceanic hindcast simulations at high resolution suggest that the Atlantic MOC is bistable. Issue 12 (19th June 2013) - Deshayes, J.; Tréguier, A.‐M.; Barnier, B.; Lecointre, A.; Sommer, J. Le; Molines, J.‐M.; Penduff, T.; Bourdallé‐Badie, R.; Drillet, Y.; Garric, G.; Benshila, R.; Madec, G.; et al.
Abstract : [1] All climate models predict a freshening of the North Atlantic at high latitude that may induce an abrupt change of the Atlantic Meridional Overturning Circulation (hereafter AMOC) if it resides in the bistable regime, where both a strong and a weak state coexist. The latter remains uncertain as there is no consensus among observations and ocean reanalyses, where the AMOC is bistable, versus most climate models that reproduce a mono‐stable strong AMOC. A series of four hindcast simulations of the global ocean at 1/12° resolution, which is presently unique, are used to diagnose freshwater transport by the AMOC in the South Atlantic, an indicator of AMOC bistability. In all simulations, the AMOC resides in the bistable regime: it exports freshwater southward in the South Atlantic, implying a positive salt advection feedback that would act to amplify a decreasing trend in subarctic deep water formation as projected in climate scenarios. Key Points: Simulated AMOC freshwater transport in South Atlantic depends on resolution AMOC in high resolution hindcasts exports freshwater southward, on average AMOC freshwater export has large variability at intra‐seasonal timescale